THE PROMOTION OF A NON-CAPITALIST ECONOMY: THE MONDRAGÓN GROUP - Ignacio Santa Cruz; Ainhoa Flecha; Olga Serradell (Ediciones Universidad de Salamanca, 2009)
Mondragón is at present the seventh entrepreneurial group in Spain according to sales volume and the third according to employment. As a cooperative, it offers a non-capitalist alternative of success, demonstrating that social transformation is possible and invalidating the theories of reproduction, which defend that education can not contribute to the overcoming of social inequalities. The present article analyses the importance given to education by Mondragón throughout its 50 years of history, making out of it a key factor both for the corporation's success as well as for the improvement of the life condition of those who participate in this experience.